2021
DOI: 10.1101/2021.10.20.21265239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of BNT162b2 Vaccine in Patients with Inflammatory Bowel Disease on Infliximab Combination Therapy: A Multicenter Prospective Study

Abstract: BackgroundVaccination is a promising strategy to protect vulnerable groups like inflammatory bowel disease (IBD) patients against COVID-19 and associated severe outcomes. COVID-19 Vaccines clinical trials excluded IBD patients taking infliximab with azathioprine or 6-mercaptopurine (infliximab combination). Therefore, we sought to evaluate serologic responses to COVID-19 vaccination with the mRNA vaccine, BNT162b2 in IBD patients receiving infliximab combination therapy compared to healthy participants.Methods… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These included 11 prospective studies, seven retrospective studies and three survey‐based studies. 16 , 17 , 18 , 19 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The PRISMA Flow chart is shown in Figure 1 . The study details are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While many studies have reported the clinical findings of hospitalised COVID‐19 patients, hospitals and healthcare staff globally remain overwhelmed. Though the development of vaccines against COVID‐19 17–20 signals hope for controlling the pandemic, tens of thousands of new cases are being reported every day and hospital staff need to be able to predict which patients are more likely to succumb to a severe form of COVID‐19, ARDS, ICU admission, or even death.…”
Section: Introductionmentioning
confidence: 99%